Bacteriology in Diagnosing Oral Odontogenic Infections: A Scoping Review - Hazhiyyah, Nabila Ghassania; Dewi, Warta; Balafif, Felisha Febriane (Journal of Syiah Kuala Dentistry Society, 2023)
Background: Odontogenic infection is an invasion of pathogenic microbes that originate from the tooth or its supporting structures and can spread to the surrounding tissue. Bacteriological examination to support the diagnosis. Objective: This study aims to discuss the role of bacteriological examination in helping to diagnose odontogenic infections. Method: Scoping review research type. Search for research gaps using the PCC strategy. PubMed, Scopus, ScienceDirect and Google Scholar databases were used to search for articles by entering keywords using Boolean Operators. Reporting of scoping review results using PRISMA-ScR guidelines. Results: Oral Streptococcus species in caries samples included S. mutans, S. salivarius, S. mitis and S. sanguis with the dominant bacteria being S. mutans. Results: The highest bacterial prevalence of odontogenic infections was Staphylococcus bacteria with high sensitivity to penicillin antibiotics. Periodontal pocket samples showed the highest differences in bacterial prevalence from the three articles, including Staphylococcus aureus, Fusobacterium nucleatum and Actinobacillus actinomycetemcomitans. Enterococcus was the dominant bacteria in two articles with samples taken from root canals. Odontogenic abscess samples showed that Gram-positive bacteria were more dominant than Gram-negative bacteria, which were the most common in the culture results of abscess patients. The spread of odontogenic infections in the facial space shows that Methicillin resistant Staphylococcus aureus (MRSA) strains are the dominant bacteria found. Conclusion: Bacteriological examination should be carried out to show the dominant bacteria that cause odontogenic infections, so that it has benefits to support the diagnosis and treatment plan by the dentist